Radiology imaging delays as independent predictors of length of hospital stay for emergency medical admissions. Issue 9 (September 2016) - Cournane, S.; Conway, R.; Creagh, D.; Byrne, D.G.; Sheehy, N.; Silke, B.
Abstract : Aim: To investigate the extent to which the time to completion for computed tomography (CT), magnetic resonance imaging (MRI), and ultrasound could be shown to influence the length of stay and costs incurred while in hospital, while accounting for patient acuity. Materials and methods: All emergency admissions, totalling 25, 326 imaging investigations between 2010–2014 were evaluated. The 50 th, 75 th, and 90 th centiles of completion times for each imaging type was entered into a multivariable truncated Poisson regression model predicting the length of hospital stay. Estimates of risk (odds or incidence rate ratios [IRRs]) of the regressors were adjusted for acute illness severity, Charlson comorbidity index, chronic disabling disease score, and sepsis status. Quantile regression analysis was used to examine the impact of imaging on total hospital costs. Results: For all imaging examinations, longer hospital lengths of stay were shown to be related to delays in imaging time. Increased delays in CT and MRI were shown to be associated with increased hospital episode costs, while ultrasound did not independently predict increased hospital costs. The magnitude of the effect of imaging delays on episode costs were equivalent to some measures of illness severity. Conclusion: CT, MRI, and ultrasound are undertaken in patients with differing clinical complexity; however, even with adjustment for complexity, the time delay in a more expeditious radiological service could potentially shorten the hospital episode and reduce costs. Highlights: There are differing clinical complexities for patients depending on the modality. A predictive risk model, incorporating advanced imaging, was devised. Inpatients delays in radiology imaging associated with longer LOS. Inpatients who underwent radiology imaging associated with increased hospital costs.